Conflict avoidance algorithm between mobility robustness optimization and load balancing functions - Demir, Çağrı (Graduate School, 2023)
Providing seamless connectivity and mobility to the end users in cellular networks have always been a big challenge for the service providers. With the evolution of the cellular networks and the increased user density, this challenge became more crucial. Operators and vendors are working to enable new features to meet these challenges and provide better quality of service (QoS) to the end user. On the other hand, developments in cellular communication networks increased system complexity and made maintaining, organizing, and sustaining the network infrastructure harder. Additionally, reducing the capital expenditures (CAPEX) and operational expenditures (OPEX) emerged. These changes in the requirements and the conditions, brings out the necessity of more autonomous cellular networks. As a result, self-organizing network (SON) concept introduced to address aforementioned issues. SON is a concept proposed in 3rd generation partnership project (3GPP) to achieve more autonomous cellular network. The idea is to create a cellular network which can be able to configure, optimize, heal, and coordinate itself. For this purpose, various SON functions introduced for different functions of cellular network, such as mobility management, random access (RA) optimization, energy efficiency etc. One of the most common SON functions utilized in cellular communication is mobility management (MM) based solutions and in this thesis, we will analyze and propose a solution to provide seamless mobility management experience. In response to the high demand for being connected anytime and anywhere, mobile networks are being evolved towards sixth generation of mobile networks (6G). At the same time, this brings more complexity to cellular networks. Increased demand also requires the SON concept to be more advanced and self-coordinated. One of the key aspects of accomplishing more advanced and coordinated SONs is conflict avoidance. The central focus of this thesis is to provide conflict-aware SON function to the literature. To accomplish this, first, we provided detailed analysis of SON functions in MM to have deeper understanding of the SON concept with its challenges for 5G and beyond. Additionally, the main SON algorithms related to MM, such as mobility load balancing (MLB) and mobility robustness optimization (MRO) are discussed with references to related literature. On the basis of this analysis and understanding, we proposed a solution to accomplish conflict-avoidance in mobility management related SON functions. Proposed algorithm designed based on the user-specific solution approach. Main reason is to utilize from user-specific approach is to be able to manage each user attached to the network individually. Particularly, the algorithm collects the network key performance indicators (KPIs) of the cell and if it detects anomaly in the KPIs, SON algorithm is triggered automatically to take corrective actions. Once the SON function activated in the cell, the information about the SON activation sent to the neighbor cells to take them necessary actions for the users incoming from SON active cell. In the meantime, SON algorithm collects the load and location information from all users individually in the SON active cell and calculates the specific handover measurement offset for each user. Accordingly, new unique handover control parameter (HCP) configuration sent to each user individually. Thanks to this design approach, algorithm can provide more specific solutions for users specifically and improves the QoS. It also achieves improvement on signaling overhead and handover KPIs. Performance of the algorithm is evaluated by comparing the results with MLB, MRO, and disabled SONs scenarios. Overall, an average improvement of 23% was achieved across all KPIs. Simulation result details are also shared in the thesis. System simulation is performed in C++ based open-source simulation environment which has built-in fourth generation of mobile networks (4G) protocol stack and handover features. To implement the proposed algorithm and other algorithms for comparison purposes, we have modified the source code of the simulation tool and developed extra functions in it. Finally, we have achieved an end-to-end cellular simulation environment to measure the performance of the proposed algorithm. Thanks to the simulation tool, it enables us to simulate the cellular network with the different settings and helps us to perform the measurements in the environment which mimic the real network conditions with extensive feature set. This also enables us to comment confidently on simulation results that are similar to real network implementations. The thesis is concluded with the simulation results and the final comments. Results show that proposed algorithm achieves better performance in terms of service continuity and mobility performance. It also shows that overall system throughput distributed among the cells more evenly. As user-based approach provides specialized solutions for the user equipment (UE) individually, it is improving the system performance of both MLB and MRO functions and eliminates the conflict problem.
Hareketlilik optimizasyonu ve yük dengeleme fonksiyonları için çatışma önleme algoritması
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Mobility robustness optimization; Hareketlilik optimizasyonu; Load balancing functions; Yük dengeleme fonksiyonları; Celullar networks; Hücresel ağlar